Integrating Embodied Cognition and Information Processing: A Combined Model of the Role of Gesture in Children's Mathematical Environments - Gordon, Raychel; Ramani, Geetha B. (Frontiers in Psychology, 2021)
Children learn and use various strategies to solve math problems. One way children’s math learning can be supported is through their use of and exposure to hand gestures. Children’s self-produced gestures can reveal unique, math-relevant knowledge that is not contained in their speech. Additionally, these gestures can assist with their math learning and problem solving by supporting their cognitive processes, such as executive function. The gestures that children observe during math instructions are also linked to supporting cognition. Specifically, children are better able to learn, retain, and generalize knowledge about math when that information is presented within the gestures that accompany an instructor’s speech. To date, no conceptual model provides an outline regarding how these gestures and the math environment are connected, nor how they may interact with children’s underlying cognitive capacities such as their executive function. In this review, we propose a new model based on an integration of the information processing approach and theory of embodied cognition. We provide an in-depth review of the related literature and consider how prior research aligns with each link within the proposed model. Finally, we discuss the utility of the proposed model as it pertains to future research endeavors.